1993
DOI: 10.1111/j.1744-7348.1993.tb04936.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of growth, yield and lodging response of lentil to phosphorus by paclobutrazol

Abstract: A foliar application of paclobutrazol (1 litre a.i. ha-') was applied before flowering of lentils grown with different levels of phosphorus (0, 20, 40, 60, 80 and 100kg P205 ha-'). Increasing amounts of P up to 80kg ha-' increased plant height, crop dry matter and grain yields but also increased crop lodging. Paclobutrazol decreased plant height and lodging and increased grain yield. Maximum yields were obtained with a combination of 80 kg P ha-' and paclobutrazol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…All these results are consistent with those obtained from other species in which GA synthesis was manipulated using plant growth regulators, as for yield (i.e. Zhou and Xi 1993;Gill and Singh 1993;Isoda 2003a, 2003b;Mohapatra and Mohapatra 2005), number and biomass of reproductive organs (Mohapatra and Mohapatra 2005), and increased SPAD values Isoda 2003a, 2003b;Mohapatra and Mohapatra 2005). Reduction in branch leaf area and branch biomass under Paclobutrazol treatment resembles the results from perennial ryegrass (Lolium perenne L.; Young et al 1996), rice (Yim et al 1997) and wheat (Guoping 1997), and differs from peanut (Arachis hypogaea L.) and Brassica carinata A.…”
Section: Discussionsupporting
confidence: 88%
“…All these results are consistent with those obtained from other species in which GA synthesis was manipulated using plant growth regulators, as for yield (i.e. Zhou and Xi 1993;Gill and Singh 1993;Isoda 2003a, 2003b;Mohapatra and Mohapatra 2005), number and biomass of reproductive organs (Mohapatra and Mohapatra 2005), and increased SPAD values Isoda 2003a, 2003b;Mohapatra and Mohapatra 2005). Reduction in branch leaf area and branch biomass under Paclobutrazol treatment resembles the results from perennial ryegrass (Lolium perenne L.; Young et al 1996), rice (Yim et al 1997) and wheat (Guoping 1997), and differs from peanut (Arachis hypogaea L.) and Brassica carinata A.…”
Section: Discussionsupporting
confidence: 88%
“…Paclobutrazol, applied as a spray, significantly reduces the accumulation of carbohydrates in leaves and promotes rapid and effective transfer of the products of photosynthesis to roots, making the roots and stems thicker and stronger, thereby checking not only excessive growth of above-ground parts (Burrows et al 1992) but also the plant's tendency to lodge. Many studies have confirmed that paclobutrazol mainly inhibits the growth of aboveground parts, reduces nutrient accumulation in stems (Gill and Singh 1993) and promotes the transport and distribution of nutrients to roots and the growth of roots (Rieger and Scalabrelli 1990). Paclobutrazol also promotes the transfer of biomass accumulated during vegetative growth to seeds in significant amounts (ddo-Quaye et al 1985).…”
Section: Introductionmentioning
confidence: 99%